2017
DOI: 10.1136/injuryprev-2016-042141
|View full text |Cite
|
Sign up to set email alerts
|

Mandatory desexing of dogs: one step in the right direction to reduce the risk of dog bite? A systematic review

Abstract: There is consistent evidence that desexing dogs is associated with a reduced risk of dog bite, although the studies reflect association and may not be causal. Although recent publications have suggested desexing is associated with health and behavioural costs in some breeds, population level evidence supports desexed dogs having a longer lifespan, and being less likely to wander with the added benefit of reducing unwanted litters. Thus, mandatory desexing presents a possible opportunity for prevention of dog b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 56 publications
0
24
0
Order By: Relevance
“…Review articles exist on the topic of desexing effects on canine behavior for both the effects of gonadectomy [5,196] and GnRH superagonist treatment [197]. Most studies on behavioral changes associated with desexing published thus far have been specific to male dogs, while comparably few of them have also included or focused on behavior in gonadectomized female dogs.…”
Section: Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…Review articles exist on the topic of desexing effects on canine behavior for both the effects of gonadectomy [5,196] and GnRH superagonist treatment [197]. Most studies on behavioral changes associated with desexing published thus far have been specific to male dogs, while comparably few of them have also included or focused on behavior in gonadectomized female dogs.…”
Section: Behaviormentioning
confidence: 99%
“…A systematic literature review based on observational studies of dog bite risk concluded that five out of six of the articles considered showed that intact dogs were more likely than desexed dogs to cause bite injuries; however, the authors also concluded that the available data was insufficient to estimate the effect size, and that all studies considered were observational case-control studies rather than interventional studies [196]. All of these studies were based on dogs from the US and/or Canada, and in this context, as is the case for health outcomes, it should be considered that desexing may act as a proxy for overall better animal husbandry standards in these populations.…”
Section: Bite Injury Riskmentioning
confidence: 99%
“…Indeed, following a systematic review of the literature D'Onise et al report consistent evidence that desexing dogs is associated with a reduced risk of dog bites. 8 However, while we had a higher number of intact males presented for traumatic proptosis, gender and neutering did not affect the likelihood of vision at the last recheck. Gilger et al also had a higher proportion of intact male patients in their study, but they did not analyze the effect of gender and neutering on outcome.…”
Section: Discussionmentioning
confidence: 66%
“…The high number of sexually intact male dogs with proptosis is not surprising since intact male dogs are at a higher risk for trauma, as they tend to be more involved in dog fights. Indeed, following a systematic review of the literature D’Onise et al report consistent evidence that desexing dogs is associated with a reduced risk of dog bites . However, while we had a higher number of intact males presented for traumatic proptosis, gender and neutering did not affect the likelihood of vision at the last recheck.…”
Section: Discussionmentioning
confidence: 98%
“…Other research pointed to unneutered male dogs as the most frequent perpetrators of bites [10,11], with castration reducing the risk [12]. Other dog traits linked to bites included the size of the dog, with larger dogs more likely to bite and with greater severity [13].…”
Section: Introductionmentioning
confidence: 99%